Vergleich der Genauigkeit zweier Methoden zur Kariesdetektion in einer epidemiologischen Feldstudie - Uebereck, Constanze Friederike; Kühnisch, Jan; Taschner, Michael; Frankenberger, Roland; Krämer, Norbert; Michel, René (Oralprophylaxe und Kinderzahnheilkunde, 2022)
Aim: In the course of the 6th nationwide epidemiological schoolchildren's oral health study, examination standards in caries diagnosis in Bavaria had to be adapted to the specifications of the German Working Group for Promotion of Youth Dental Care (Deutsche Arbeitsgemeinschaft für Jugendzahnpflege, DAJ). However, it was questionable whether the recorded data would be comparable with earlier examination outcomes. The present study therefore aimed to investigate whether different specifications from Bavaria (BA) and Germany (DAJ) lead to different DMF-T/S values. Methods: From the representative sample provided by the GESIS Leibniz Institute in Mannheim, Germany, 965 Bavarian sixth graders from 50 schools were assessed twice and independently between October 15, 2015 and June 20, 2016. All investigators qualified via online calibration (κ ≥0.65). Control investigators (CI; n=3) underwent an additional local briefing. Pupils were investigated independently by two investigators. Study investigators (SI; n=21) used conventional DAJ equipment (WHO probe, mirror, 20 W lamp, cotton dental rolls); CI used enhanced BA equipment (50 W lamp, stream of air, magnifying loops). The DMF-T/S values were recorded, initial caries screened, and the Significant Caries (SiC) index was computed. Two-sample comparisons were carried out using the t-test, and the analysis of variance was used for multiple sample analyses. Results: In all, 53.4% (CI) and 63% (SI) of children (average age 12.3 years) were caries-free. Mean DMF(T) was 1.65 (DMFS=2.33) for the CI group and 0.89 (DMFS=1.31) for the SI group. Calculated SiC-DMF(T) value of CI was 4.18, while SI was 2.54. The calculated SiC-DMF(S) values were also different (CI: 6.15/SI: 3.78). CI found significantly more initial caries (2.04) than SI (1.16). The data analysis showed that control examiners detected significantly higher experience of caries compared to the study investigators. Conclusion: The results show a discrepancy in the detection of caries in 11- to 14-year-old Bavarian pupils, with the better-equipped control examiners detecting a significantly greater caries experience than the study examiners. Consequently, the equipment used by investigators in epidemiological studies has a significant impact on the accuracy of caries diagnosis. Therefore, this should be taken into account for the planning of further epidemiological studies.
CRIS-Team Scopus Importer:2024-12-16
Keywords: Calibration; Caries diagnosis; Caries experience; Oral health; Risk of caries